China?s water pricing reforms for irrigation: effectiveness and impact - Liao, Yongsong; Gao, Z.; Bao, Z.; Huang, Q.; Feng, G.; Xu, D.; Cai, J.; Han, H.; Wu, W. (International Water Management Institute, 2008)
Irrigation occupies a central position in China?s crop production. However, due to low per capita water resources, much worse, unevenly distributed over regions and time and the rapid increase of water diversions to non-irrigation sectors, irrigation water shortages have become a very serious problem. Without the adoption of effective measures this problem may even threaten China?s food security. Currently, irrigation efficiency is very low in general, irrigation water prices cannot fully recover water supply costs, and irrigation facilities are aging due to the lack of funding for O&M (operation & maintenance). Since water prices are regulated by the government, and not determined by the market, water prices did not work effectively in water allocation. The adoption of more economic incentive measures, such as increasing water prices, has become the main strategy of the Chinese government. Since 1 January 2004, China has carried out a new water pricing regulation. The main objectives of this regulation are that water price should be increased to fully recover water supply cost and that water should be treated as a market good. In non-irrigation sectors, the consensus is that water price could be charged to fully recover water supply cost. However, there is still controversy over the charge of irrigation water pricing. Indeed, increasing water price to fully recover supply cost may seriously affect grain production, and farmers? income. Past studies in China on these issues mainly focused on the theoretical aspects of the problem, analyzing whether irrigation water price should be increased or not. Little studies have quantified the potential impact of the reforms in China. The following questions need to be elaborated: Are irrigation water pricing reforms effective?; What are the attitudes of the farmers towards the reforms?; How do farmers respond to water pricing reforms?; What comprehensive methods should be adopted to achieve the goals of the reforms?